Copper-clad laminate and method of forming the same

A copper-clad laminate with a resin matrix and ceramic filler coating addresses stability and signal loss issues, enhancing performance in high-frequency applications by using a specific dielectric coating composition.

JP2025000662AInactive Publication Date: 2025-01-07SAINT GOBAIN PERFORMANCE PLASTICS CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024155074
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-07-28
Filing Date
2024-09-09
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing copper-clad laminates for printed circuit boards face challenges in maintaining thermomechanical stability, withstanding high temperatures, resisting moisture absorption, and minimizing signal loss and crosstalk, especially in high-frequency applications, due to inadequate dielectric materials.

Method used

A copper-clad laminate comprising a copper foil layer covered by a dielectric coating made of a resin matrix and ceramic filler component, with specific particle size distributions and average thickness, enhancing thermal stability and reducing signal loss.

Benefits of technology

The laminate provides improved thermomechanical stability, resistance to moisture, and reduced signal loss, enabling high-frequency applications without deformation at elevated temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025000662000001_ABST
    Figure 2025000662000001_ABST
Patent Text Reader

Abstract

To provide an improved copper-clad laminate that can be used in printed circuit boards and other high-frequency applications.SOLUTION: The present disclosure relates to a copper-clad laminate that may include a copper foil layer 202 and a dielectric coating 205 overlying the copper foil layer. The dielectric coating may include a resin matrix component 210 and a ceramic filler component 220. The ceramic filler component may include a first filler material. The dielectric coating may have an average thickness of about 20 microns or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to copper clad laminates and methods of forming the same. In particular, the present disclosure relates to a dielectric coating. The present invention relates to a copper clad laminate having a bonding layer and a method for forming the same. [Background technology]

[0002] Copper-clad laminate (CCL) is a laminate made of conductive copper foil on or between two layers. Subsequent operations may result in such CCLs being printed on the printed circuit board. Converted into a printed circuit board (PCB). Used to form PCBs When the conductive copper foil is to be etched, the conductive copper foil is selectively etched to produce through holes drilled between the layers. and metallized, i.e. plated, to provide electrical conductivity between layers in a multilayer PCB. Therefore, CCL must exhibit excellent thermomechanical stability. B is also routinely exposed to excessively high temperatures not only during use but also during manufacturing operations such as soldering. They are therefore capable of functioning at continuous temperatures above 200°C without deformation. It must be able to withstand dramatic temperature fluctuations while resisting moisture absorption. The dielectric layer of L acts as a spacer between the conductive layers, blocking electrical conductivity. Signal loss and crosstalk can be minimized. The dielectric constant of the dielectric layer (absolute dielectric constant) The lower the polarization coefficient, the faster the speed of an electrical signal passing through the layer. A low dielectric loss tangent, which is temperature and frequency dependent, is very important for high frequency applications. Thus, an improved dielectric material that can be used in PCB and other high frequency applications. and a dielectric layer is desired. Summary of the Invention

[0003] According to a first embodiment, a copper clad laminate includes a copper foil layer and a dielectric coating covering the copper foil layer. The dielectric coating may include a resin matrix component and a ceramic filler component. and a dielectric component. The ceramic filler component may include a first filler material. The coating may have an average thickness of about 20 microns or less.

[0004] According to another aspect, a copper clad laminate includes a copper foil layer, a dielectric coating overlying the copper foil layer, and The dielectric coating may include a resin matrix component and a ceramic filler component. The ceramic filler component may include a first filler material. The particle size distribution of the filler material is at least about 0.2 microns and no greater than about 1.6 D 10 , few D at least about 0.5 microns and not more than about 2.7 microns 50 , and at least about 0.8 mm D less than about 4.7 microns 90 may have:

[0005] According to yet another aspect, the copper clad laminate comprises a copper foil layer and a dielectric coating overlying the copper foil layer. The dielectric coating may include a resin matrix component and a ceramic filler. and the ceramic filler component may include a first filler material. The filler material has an average particle size of about 5 microns or less and a particle size distribution span of about 5 or less. The PSDS may further comprise a particle size distribution span (PSDS), 90 -D 1 0 ) / D 50 is equal to D 90 is the D of the first filler material90 Equivalent to particle size distribution measurement , D 10 is the D of the first filler material 10 D is equal to the particle size distribution measurement 50 The first Filler material D 50 Equivalent to particle size distribution measurement.

[0006] According to another aspect, the printed circuit board may include a copper clad laminate. The copper foil layer may include a foil layer and a dielectric coating overlying the copper foil layer. The dielectric coating may include a resin The ceramic filler component may include a matrix component and a ceramic filler component. The dielectric coating may include a first filler material. The dielectric coating may have an average thickness of about 20 microns or less. It may have a thickness.

[0007] According to yet another aspect, the printed circuit board may include a copper clad laminate. , a copper foil layer, and a dielectric coating overlying the copper foil layer. The dielectric coating may include The ceramic filler may include a resin matrix component and a ceramic filler component. The component may include a first filler material. The particle size distribution of the first filler material is at least D of about 0.2 microns and about 1.6 or less 10 , at least about 0.5 microns and about 2.7 Submicron D 50 and D of at least about 0.8 microns and not more than about 4.7 microns. 90 may have:

[0008] According to another aspect, the printed circuit board may include a copper clad laminate. The copper foil layer may include a foil layer and a dielectric coating overlying the copper foil layer. The dielectric coating may include a resin The ceramic filler component may include a matrix component and a ceramic filler component. The filler material may include a first filler material having an average particle size of about 5 microns or less. diameter, and a particle size distribution span (PSDS) of about 5 or less, the PSDS being (D 90 - D 10 ) / D 50 is equal to D 90 is the D of the first filler material 90 Particle size distribution measurement Shik, D 10 is the D of the first filler material 10 D is equal to the particle size distribution measurement 50 The first D of filler material 50 Equivalent to particle size distribution measurement.

[0009] According to another aspect, a method of forming a copper clad laminate includes providing a copper foil layer and 3. Combining the trix precursor component and the ceramic filler precursor component to form a forming mixture. and forming the forming mixture into a dielectric coating over the copper foil. The ceramic filler precursor component may include a first filler precursor material. The coating may have an average thickness of about 20 microns or less.

[0010] According to yet another aspect, a method of forming a copper clad laminate includes providing a copper foil layer and The oil matrix precursor component and the ceramic filler precursor component are combined to form a mixture. forming a dielectric coating over the copper foil; and forming the forming mixture into a dielectric coating over the copper foil. The ceramic filler precursor component may include a first filler precursor material. The particle size distribution of the filler material is at least about 0.2 microns and no greater than about 1.6 D 10 , D of at least about 0.5 microns and no more than about 2.7 microns 50 , and at least about 0. 8 microns and D less than about 4.7 microns 90 may have:

[0011] According to another aspect, a method of forming a copper clad laminate includes providing a copper foil layer and 3. Combining the trix precursor component and the ceramic filler precursor component to form a forming mixture. and forming the forming mixture into a dielectric coating over the copper foil. The ceramic filler precursor component may include a first filler precursor material. The filler precursor material has an average particle size of about 5 microns or less and a particle size distribution span (P The PSDS may further comprise (D 90 -D 10 ) / D 50 is equal to D 90 teeth, D of the first filler precursor material 90 D is equal to the particle size distribution measurement 10 The first filler D of precursor material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler precursor material 50 Equivalent to particle size distribution measurement.

[0012] According to another aspect, a method of forming a printed circuit board includes providing a copper foil layer; The resin matrix precursor component and the ceramic filler precursor component are combined to form a mixture. forming a dielectric coating over the copper foil; and forming the forming mixture into a dielectric coating over the copper foil. The ceramic filler precursor component may include a first filler precursor material. The dielectric coating may have an average thickness of about 20 microns or less.

[0013] According to yet another aspect, a method of forming a printed circuit board includes providing a copper foil layer. The resin matrix precursor component and the ceramic filler precursor component are mixed together to form a mixture. forming a mixture and forming the mixture into a dielectric coating over the copper foil. The ceramic filler precursor component may include a first filler precursor material. The particle size distribution of the first filler material is at least about 0.2 microns and no greater than about 1.6 D 10 , D of at least about 0.5 microns and not more than about 2.7 microns 50 , and at least D of about 0.8 microns and less than or equal to about 4.7 microns 90 may have:

[0014] According to another aspect, a method of forming a printed circuit board includes providing a copper foil layer; The resin matrix precursor component and the ceramic filler precursor component are combined to form a mixture. forming a dielectric coating over the copper foil; and forming the forming mixture into a dielectric coating over the copper foil. The ceramic filler precursor component may include a first filler precursor material. The filler precursor material of 1 has an average particle size of about 5 microns or less and a particle size distribution span of about 5 or less. The PSDS may further include a program for determining whether the 90 -D 10 ) / D 50 is equal to D 9 0 is the D of the first filler precursor material 90 D is equal to the particle size distribution measurement 10 The first D of filler precursor material 10 D is equal to the particle size distribution measurement 50 is a first filler precursor material Fee D 50 Equivalent to particle size distribution measurement. [Brief description of the drawings]

[0015] Embodiments are illustrated by way of example and not limitation in the accompanying figures. [Figure 1] 1 includes diagrams illustrating a method of forming a copper clad laminate according to embodiments described herein. [Diagram 2] 1 includes diagrams showing the configuration of a copper clad laminate formed in accordance with embodiments described herein. [Diagram 3] 1 includes diagrams illustrating a method of forming a printed circuit board according to embodiments described herein. [Figure 4] 1 includes diagrams illustrating the configuration of a printed circuit board formed in accordance with embodiments described herein.

[0016] Skilled artisans will appreciate that elements in the figures are illustrated for simplicity and clarity and are not necessarily drawn to scale. Understand that it is not painted on the street. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The following description focuses on specific implementations and embodiments of the teachings. are provided to help describe certain embodiments and are not intended to limit the scope of the present disclosure or teachings. The disclosure and the claims provided herein should not be construed as limitations on the scope or applicability of the present invention. It will be understood that other embodiments can be used based on the teachings.

[0018] The terms "comprises," "comprising," and "includes" "including," "has," "having," or any of these terms Other variations of the invention are intended to cover non-exclusive inclusions. For example, changing the list of features to The methods, articles, or apparatuses that include, but are not necessarily limited to, those features expressly described herein. Any other features not specifically recited or inherent to such method, article, or apparatus. Further, unless expressly stated to the contrary, "or" refers to an inclusive or and not an exclusive or. For example, condition A or B can be satisfied by one of the following: satisfied: A is true (or exists) and B is false (or does not exist), A is false (or not) and B is true (or exists), and both A and B are It is true (or exists).

[0019] The embodiments described herein generally comprise a copper foil layer and a dielectric coating overlying the copper foil layer. According to certain embodiments, the present invention is directed to a copper clad laminate that may include a dielectric coating. The coating may include a resin matrix component and a ceramic filler component.

[0020] Referring first to the method of forming a copper clad laminate, FIG. 1 includes a diagram illustrating a forming method 100 for forming a copper clad laminate according to an embodiment. According to an embodiment, the forming method 100 includes a first step 110 of providing a copper foil layer and a resin matrix. The filler precursor component and the ceramic filler precursor component are combined to form a forming mixture. A second step 120 includes forming the mixture into a dielectric coating over the copper foil layer to form a copper. and a third step 130 of forming a laminate.

[0021] According to certain embodiments, the ceramic filler precursor components are formed by the forming method 100. A first filler precursor that may have specific properties that may improve the performance of the copper clad laminate formed therefrom. The material may include

[0022] According to certain embodiments, the first filler precursor material may have a particular size distribution. For purposes of the embodiments described herein, the particle size distribution of the material, e.g., the first filler - The particle size distribution of the precursor material is the particle size distribution D value D 10 , D 50 , and D 90 Any combination of The particle size distribution can be described using the D 10 A value is the number of particles smaller than which 10% of the particles The diameter is defined as the diameter value above which 90% of the particles are larger. 5 0 The value is the particle size value below which 50% of the particles are smaller and above which 50% of the particles are larger. D from the particle size distribution is defined as 90 A value is the value below which 90% of the particles are smaller than the particle size. A particle size value above which 10% of the particles are larger is defined as the particle size value above which 10% of the particles are larger. For purposes of the present embodiment, particle size measurements of certain materials are performed using laser diffraction spectroscopy.

[0023] According to a particular embodiment, the first filler precursor material has a particular size distribution D 10 Value For example, D of the first filler precursor material 10 is at least about 0.2 microns, For example, at least about 0.3 microns, or at least about 0.4 microns, or at least At least about 0.5 microns, or at least about 0.6 microns, or at least about 0.7 microns or at least about 0.8 microns, or at least about 0.9 microns, or at least at least about 1.0 microns, or at least about 1.1 microns, or even at least about 1.2 According to yet another embodiment, the D of the first filler material may be 10 is about 1 0.6 microns or less, for example, about 1.5 microns or less, or even about 1.4 microns or less. D of the first filler precursor material 10 is one of the above minimum and maximum values. It will be understood that the first filler precursor may be any value between and including the above. Body material D 10 is a range between and including any of the above minimum and maximum values. It will be further appreciated that the present invention may be practiced in accordance with the present invention.

[0024] According to another embodiment, the first filler precursor material has a particular size distribution D 50 Has value For example, D of the first filler precursor material 50 is at least about 0.5 microns, e.g. For example, at least about 0.6 microns, or at least about 0.7 microns, or at least About 0.8 microns, or at least about 0.9 microns, or at least about 1.0 microns or at least about 1.1 microns, or at least about 1.2 microns, or at least About 1.3 microns, or at least about 1.4 microns, or at least about 1.5 microns or at least about 1.6 microns, or at least about 1.7 microns, or at least About 1.8 microns, or at least about 1.9 microns, or at least about 2.0 microns , or at least about 2.1 microns, or even at least about 2.2 microns. According to yet another embodiment, the first filler material D 50 is approximately 2.7 microns or less, For example, about 2.6 microns or less, or about 2.5 microns or less, or even about 2.4 microns or less. The D of the first filler precursor material may be less than or equal to 50 is the minimum and maximum value above. It will be appreciated that the first filter may be any value between and including any of the following: D of precursor materials 50is between the minimum and maximum values ​​above and It will be further understood that the range may be inclusive.

[0025] According to another embodiment, the first filler precursor material has a particular size distribution D 90 Has value For example, D of the first filler precursor material 90 is at least about 0.8 microns, e.g. For example, at least about 0.9 microns, or at least about 1.0 microns, or at least About 1.1 microns, or at least about 1.2 microns, or at least about 1.3 microns or at least about 1.4 microns, or at least about 1.5 microns, or at least About 1.6 microns, or at least about 1.7 microns, or at least about 1.8 microns or at least about 1.9 microns, or at least about 2.0 microns, or at least About 2.1 microns, or at least about 2.2 microns, or at least about 2.3 microns or at least about 2.4 microns, or at least about 2.5 microns, or at least It may be about 2.6 microns, or even at least about 2.7 microns. According to the embodiment, the D of the first filler material 90 is about 8.0 microns or less, for example, about 7.5 microns or less, or about 7.0 microns or less, or about 6.5 microns or less, or about 6.0 microns or less 5.5 microns or less, or about 5.4 microns or less, or about 5.3 microns or less The diameter of the nanoparticles may be about 5.2 microns or less, or even about 5.1 microns or less. 1. Filler precursor material D 90 is between any of the minimum and maximum values ​​above and It will be understood that the D of the first filler precursor material may be any value including those mentioned above. 9 0 may be in a range between and including any of the minimum and maximum values ​​listed above. It will be further understood.

[0026] According to yet another embodiment, the first filler precursor material is characterized using laser diffraction spectroscopy. For example, the first filler precursor material may have a particular average particle size measured by the average particle size of the first filler precursor material. The diameter is about 10 microns or less, for example, about 9 microns or less, or about 8 microns or less, 7 microns or less, or about 6 microns or less, or about 5 microns or less, or about 4 microns or less , or about 3 microns or less, or even about 2 microns or less. The average particle size of the bulk material may be any value between and including any of the values ​​listed above. It will be understood that the average particle size of the first filler precursor material may be any of the values ​​listed above. It will be further understood that the range may be between and inclusive of any of the above.

[0027] According to yet another embodiment, the first filler precursor material is selected from the group consisting of a filler having a particular particle size distribution span ( The PSDS may be described as having (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler precursor material 90 Equivalent to particle size distribution measurement, D 10 is the D of the first filler precursor material 10 D is equal to the particle size distribution measurement 50 The first D of filler precursor material 50 Equivalent to the particle size distribution measurement. For example, the first filler precursor The PSDS of the material is about 5 or less, for example, about 4.5 or less, or about 4.0 or less, or about 3.5 The first filler precursor material may be about 2.5 or less, or about 3.0 or less, or even about 2.5 or less. The PSDS for the material may be any value between and including any of the values ​​above. It will be understood that the PSDS of the first filler precursor material may be any one of the values ​​above. It will be further understood that the range may be between and including:

[0028] According to yet another embodiment, the first filler precursor material is a filler precursor material selected from the group consisting of Brunauer-Emmett -Measured using Brunauer-Emmett-Teller (BET) surface area analysis (nitrogen adsorption) For example, the first filler precursor may be described as having a particular average surface area. The material is about 10m 2 / g or less, for example, about 9.9m 2 / g or less, or about 9.5m 2 / g or more Below, or about 9.0m 2 / g or less, or about 8.5m 2 / g or less, or about 8.0m 2 / g or less , or about 7.5m 2 / g or less, or about 7.0m 2 / g or less, or about 6.5m 2 / g or less, Or about 6.0m 2 / g or less, or about 5.5m 2 / g or less, or about 5.0m 2 / g or less, or is about 4.5m 2 / g or less, or about 4.0m 2 / g or less, or even about 3.5m 2 The following average According to yet another embodiment, the first filler precursor material may have at least Both are about 1.2m 2 / g, e.g., at least about 2.2 m 2 / g of average surface area. The average surface area of ​​the first filler precursor material is within any one of the minimum and maximum values ​​described above. It will be understood that the first filler precursor material may be any value between and including the above. The average surface area of ​​the above ranges between and including any of the minimum and maximum values. It will be further appreciated that it may be possible.

[0029] According to other embodiments, the first filler precursor material may include a specific material. According to this embodiment, the first filler precursor material may include a silica-based compound. According to an embodiment, the first filler precursor material may be a silica-based compound. According to an embodiment, the first filler precursor material may include silica. According to the present invention, the first filler precursor material may consist of silica.

[0030] According to yet another embodiment, the forming mixture comprises a specific content of a ceramic filler precursor. For example, the content of the ceramic filler precursor component may be adjusted to the first forming mixture. At least about 30% by volume, for example at least about 31% by volume, or less, based on the total volume of the article. at least about 32% by volume, or at least about 33% by volume, or at least about 34% by volume, or is at least about 35% by volume, or at least about 36% by volume, or at least about 37% by volume %, or at least about 38%, or at least about 39%, or at least about 40% by volume. %, or at least about 41%, or at least about 42%, or at least about 4 3% by volume, or at least about 44% by volume, or at least about 45% by volume, or at least About 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or less At least about 49% by volume, or at least about 50% by volume, or at least about 51% by volume, or at least about 49% by volume. At least about 52% by volume, or at least about 53% by volume, or even at least about 54% by volume. According to yet another embodiment, the content of the ceramic filler precursor component may be: About 57% by volume or less, for example, about 56% by volume or less, based on the total volume of the formed mixture, or even The ceramic filler precursor content may be less than or equal to about 55% by volume. It will be understood that the value may be any value between and including any of the maximum values. The content of the ceramic filler precursor component is within the range of the minimum and maximum values ​​described above. It will be further understood that the range may be between and including the above.

[0031] According to yet another embodiment, the ceramic filler precursor component comprises a first For example, the content of the first filler precursor material may be At least about 80% by volume, for example at least At least about 81% by volume, or at least about 82% by volume, or at least about 83% by volume, or less at least about 84% by volume, or at least about 85% by volume, or at least about 86% by volume, or at least about 87% by volume, or at least about 88% by volume, or at least about 89% by volume; Or even at least about 90% by volume. According to yet another embodiment, the first filter The content of the ceramic filler precursor material was approximately 100 parts by volume relative to the total volume of the ceramic filler precursor components. % by volume or less, for example, about 99% by volume or less, or about 98% by volume or less, or about 97% by volume or less; or about 96% by volume or less, or about 95% by volume or less, or about 94% by volume or less, or about 93% by volume or less % or less, or even about 92 vol. % or less. The content of the first filler precursor material is may be any value between and including any of the minimum and maximum values ​​listed above. It will be understood that the content of the first filler precursor material is within the above minimum and maximum values. It will be further understood that the range may be between and inclusive of any of the above.

[0032] According to yet another embodiment, the ceramic filler precursor component comprises a second filler precursor. The material may include a body material.

[0033] According to other embodiments, the second filler precursor material may include certain materials. For example, the second filler precursor material may be a high dielectric constant ceramic material, e.g., a dielectric constant of at least about 14. According to certain embodiments, the second filler may include a ceramic material having a dielectric constant of The precursor material can be any high dielectric constant ceramic material, such as TiO 2 , SrTiO 3 , Zr Ti 2 O 6 , MgTiO 3 , CaTiO 3 , BaTiO 4 or any combination thereof It may include.

[0034] According to yet another embodiment, the second filler precursor material is TiO 2 It may include. According to another embodiment, the second filler precursor material is TiO 2 It may consist of:

[0035] According to yet another embodiment, the ceramic filler precursor component comprises a specific content of the second For example, the content of the second filler precursor material may be At least about 1% by volume, for example at least About 2% by volume, or at least about 3% by volume, or at least about 4% by volume, or at least about 5% by volume, or at least about 6% by volume, or at least about 7% by volume, or at least about 8% by volume %, or at least about 9% by volume, or at least about 10% by volume. According to an embodiment, the content of the second filler precursor material is a ceramic filler precursor material. About 20% by volume or less, for example, about 19% by volume or less, or about 18% by volume or less, based on the total volume of the component. or less than about 17% by volume, or less than about 16% by volume, or less than about 15% by volume, or less than about 14% by volume % or less by volume, or about 13% or less by volume, or about 12% or less by volume. The content of the precursor material is between and including any of the minimum and maximum values ​​listed above. It will be understood that the content of the second filler precursor material can be any value. It is further understood that the range may be between and including any of the minimum and maximum values. Let it be understood.

[0036] According to yet another embodiment, the ceramic filler precursor component has a specific content of amorphous For example, the ceramic filler precursor component may comprise at least about 98% may further comprise at least about 97%, such as at least about 99%, amorphous material. The content of the material may be any value between and including any of the values ​​listed above. It will be understood that the content of amorphous material may range between and including any of the values ​​recited above. It will be further understood that the range may be within the range.

[0037] According to other embodiments, the resin matrix precursor component may include specific materials. For example, the resin matrix precursor component can include a perfluoropolymer. Depending on the embodiment, the resin matrix precursor component may consist of a perfluoropolymer.

[0038] According to yet another embodiment, the perfluoropolymer of the resin matrix precursor component is , copolymer of tetrafluoroethylene (TFE), hexafluoro Copolymer of hexafluoropropylene (HFP), tetrafluoroethylene terpolymers of tetrafluoroethylene (TFE), terpolymers of tetrafluoroethylene (TFE), or any combination thereof. According to the report, the perfluoropolymer of the resin matrix precursor is tetrafluoroethylene. copolymers of tetrafluoroethylene (TFE), copolymers of hexafluoropropylene (HFP), terpolymers of trifluoroethylene (TFE), or any combination thereof obtain.

[0039] According to yet another embodiment, the perfluoropolymer of the resin matrix precursor component is , polytetrafluoroethylene (PTFE), perfluoro Alkoxy polymer resin (perfluoroalkoxy, PFA), fluorinated ethylene propylene (f FEP, or any combination thereof. According to yet another embodiment, the perfluoropolymer of the resin matrix precursor component is Polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PF A), fluorinated ethylene propylene (FEP), or any combination thereof obtain.

[0040] According to yet another embodiment, the forming mixture comprises a specific content of resin matrix precursor. For example, the content of the resin matrix precursor component may be determined based on the total volume of the forming mixture. at least about 45% by volume, e.g., at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least At least about 50% by volume, or at least about 51% by volume, or at least about 52% by volume, or less at least about 53% by volume, or at least about 54% by volume, or even at least about 55% by volume According to yet another embodiment, the content of the resin matrix precursor component is About 63% by volume or less, or about 62% by volume or less, or about 61% by volume or less, based on the total volume of the mixture or less than about 60% by volume, or less than about 59% by volume, or less than about 58% by volume, or even The resin matrix precursor component content is about 57% by volume or less. It will be appreciated that the value may be any value between and including any of the above values. The content of the lipid matrix precursor component is between the minimum and maximum values ​​above. It will be further understood that the range may be inclusive of any of the above.

[0041] According to yet another embodiment, the forming mixture contains a specific content of perfluoropolymer. For example, the content of the perfluoropolymer may be less than the total volume of the forming mixture. at least about 45% by volume, e.g., at least about 46% by volume, or at least about 47% by volume; or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume %, or at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume. % by volume, or at least about 54% by volume, or even at least about 55% by volume. According to yet another embodiment, the content of perfluoropolymer is 0.01 to 0.1% by volume of the forming mixture. % or less by volume, for example, about 62% or less by volume, or about 61% or less by volume, or about 60% or less by volume. % or less by volume, or about 59% or less by volume, or about 58% or less by volume, or even about 57% or less by volume. The perfluoropolymer content may be less than or equal to any of the above minimum and maximum values. It will be understood that the value may be any value between and including the above. The content of - is within the range between and including any of the minimum and maximum values ​​above. It will be further understood that this is possible.

[0042] Reference is now made to an embodiment of a copper clad laminate formed according to method 100. 2 includes a diagram of a copper clad laminate 200. As shown in FIG. 2, the copper clad laminate 200 is made of copper The copper foil layer 202 may include a foil layer 202 and a dielectric coating 205 covering the surface of the copper foil layer 202. According to certain embodiments, the dielectric coating 205 comprises a resin matrix component 210 and A ceramic filler component 220 may be included.

[0043] According to certain embodiments, the ceramic filler component 220 improves the properties of the copper clad laminate 200. The composite may include a first filler material that may have certain properties that may improve performance.

[0044] According to certain embodiments, the first filler material of the ceramic filler component 220 is: For purposes of the embodiments described herein, the particle size distribution of a material may be The particle size distribution of the first filler material in the fabric, for example, is determined by the particle size distribution D value D 10 , D 50 , and D 9 0 Any combination of D from the particle size distribution can be used to describe the particle size distribution. 10 The value is 10 The particle size is defined as the particle size value below which 90% of the particles are smaller and 90% of the particles are larger. D from particle size distribution 50 A value is a number that 50% of the particles have a value smaller than that value and 50% of the particles have a value The particle size distribution is defined as the particle size value larger than D 90 The value is 90% of the particles are This is defined as the particle size value below which 10% of the particles are larger than the value. For purposes of the embodiments described herein, particle size measurements of certain materials are performed using laser diffraction spectroscopy. This is carried out using

[0045] According to certain embodiments, the first filler material of the ceramic filler component 220 is: Specific diameter distribution D 10 For example, the D of the first filler material may have a value of 10 At least About 0.2 microns, e.g., at least about 0.3 microns, or at least about 0.4 microns. ron, or at least about 0.5 microns, or at least about 0.6 microns, or less At least about 0.7 microns, or at least about 0.8 microns, or at least about 0.9 microns lon, or at least about 1.0 micron, or at least about 1.1 microns, or even According to yet another embodiment, the first filler material may be at least about 1.2 microns. Fee D 10 is about 1.6 microns or less, for example, about 1.5 microns or less, or even about 1 The D of the first filler material may be 0.4 microns or less. 10 are the minimum and maximum values ​​above It will be appreciated that the value may be any value between and including any of the following: Filler material D10 is between and including any of the minimum and maximum values ​​above. It will be further understood that the range may be within the range.

[0046] According to another embodiment, the first filler material of the ceramic filler component 420 is, in particular, Constant diameter distribution D 50 For example, the D of the first filler material may have a value of 50 is at least about 0.5 microns, e.g., at least about 0.6 microns, or at least about 0.7 microns or at least about 0.8 microns, or at least about 0.9 microns, or at least At least about 1.0 microns, or at least about 1.1 microns, or at least about 1.2 microns or at least about 1.3 microns, or at least about 1.4 microns, or at least At least about 1.5 microns, or at least about 1.6 microns, or at least about 1.7 microns or at least about 1.8 microns, or at least about 1.9 microns, or at least at least about 2.0 microns, or at least about 2.1 microns, or even at least about 2.2 microns According to yet another embodiment, the D of the first filler material may be 50 is about 2 0.7 microns or less, for example, about 2.6 microns or less, or about 2.5 microns or less, or even The D of the first filler material may be about 2.4 microns or less. 50 is the minimum value above and It will be appreciated that the value may be any value between and including any of the maximum values. D of the first filler material 50 is between the minimum and maximum values ​​above and It will be further understood that the range may include these.

[0047] According to another embodiment, the first filler material of the ceramic filler component 420 is, in particular, Constant diameter distribution D 90 For example, the D of the first filler material may have a value of 90 is at least about 0.8 microns, e.g., at least about 0.9 microns, or at least about 1.0 microns or at least about 1.1 microns, or at least about 1.2 microns, or at least At least about 1.3 microns, or at least about 1.4 microns, or at least about 1.5 microns or at least about 1.6 microns, or at least about 1.7 microns, or at least At least about 1.8 microns, or at least about 1.9 microns, or at least about 2.0 microns or at least about 2.1 microns, or at least about 2.2 microns, or at least At least about 2.3 microns, or at least about 2.4 microns, or at least about 2.5 microns or at least about 2.6 microns, or even at least about 2.7 microns. According to yet another embodiment, the D of the first filler material 90 is approximately 8.0 microns or less For example, about 7.5 microns or less, or about 7.0 microns or less, or about 6.5 microns or less or less than about 6.0 microns, or less than about 5.5 microns, or less than about 5.4 microns or about 5.3 microns or less, or about 5.2 microns or less, or even about 5.1 microns The D of the first filler material may be 90 is one of the above minimum and maximum values. It will be understood that the value may be any value between and including the first filler material. D 90 is within the range between and including any of the minimum and maximum values ​​above. It will be further understood that this is also possible.

[0048] According to yet another embodiment, the first filler material of the ceramic filler component 220 is The first powder may have a particular average particle size as measured using laser diffraction spectroscopy. The filler material has an average particle size of about 10 microns or less, for example, about 9 microns or less, or about 8 microns or less. Cr or less, or about 7 microns or less, or about 6 microns or less, or about 5 microns or less, or can be about 4 microns or less, or about 3 microns or less, or even about 2 microns or less. The average particle size of the first filler material may be any value between and including any of the values ​​listed above. It will be understood that the average particle size of the first filler material can be any of the above values. It will be further understood that the range may be between and including any of the above.

[0049] According to yet another embodiment, the first filler material of the ceramic filler component 220 is , may be described as having a particular particle size distribution span (PSDS), , (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler material 90 Particle size Fabric measurement equals D 10 is the D of the first filler material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler material 50 Equivalent to particle size distribution measurement. For example, the first filler The PSDS of the material is about 5 or less, for example, about 4.5 or less, or about 4.0 or less, or about 3.5 The P of the first filler material may be about 3.0 or less, or even about 2.5 or less. It is understood that the SDS can be any value between and including any of the above values. It will be understood that the PSDS for the first filler material may range between and include any of the above values. It will be further understood that the range may be within the range.

[0050] According to yet another embodiment, the first filler material of the ceramic filler component 220 is , measured using Brunauer-Emmett-Teller (BET) surface area analysis (nitrogen adsorption) For example, the first filler material may be described as having a particular average surface area. , about 10m 2 / g or less, for example, about 9.9m 2 / g or less, or about 9.5m 2 / g or less, or is about 9.0m 2 / g or less, or about 8.5m 2 / g or less, or about 8.0m 2 / gm 2 / g or more Below, or about 7.5m 2 / g or less, or about 7.0m 2 / g or less, or about 6.5m 2 / g or less , or about 6.0 m 2 / g or less, or about 5.5m 2 / g or less, or about 5.0m 2 / g or less, Or about 4.5m 2 / g or less, or about 4.0m 2 / g or less, or even about 3.5m 2 below According to yet another embodiment, the first filler material may have an average surface area of ​​at least Approximately 1.2m 2 / g, e.g., at least about 2.2 m 2 The first may have an average surface area of ​​1 / g. The average surface area of ​​the filler material is between and including any of the minimum and maximum values ​​set forth above. It will be appreciated that the average surface area of ​​the first filler material may be any value including, but not limited to, any one of the following: It may be within a range between and including any of the above minimum and maximum values. Let's understand further.

[0051] According to another embodiment, the first filler material of the ceramic filler component 220 is, in particular, According to a particular embodiment, the first filler material may include a silica-based compound. According to yet another embodiment, the first filler material may comprise a silica-based compound. According to another embodiment, the first filler material may include silica. According to an embodiment, the first filler material may consist of silica.

[0052] According to yet another embodiment, the dielectric coating 205 has a specific content of ceramic. For example, the content of the ceramic filler component 220 may be At least about 30% by volume, for example at least about 10% by volume, based on the total volume of the dielectric coating 205. At least about 31% by volume, or at least about 32% by volume, or at least about 33% by volume, or less at least about 34% by volume, or at least about 35% by volume, or at least about 36% by volume, or at least about 37% by volume, or at least about 38% by volume, or at least about 39% by volume; or at least about 40% by volume, or at least about 41% by volume, or at least about 42% by volume %, or at least about 43% by volume, or at least about 44% by volume, or at least about 45% by volume % by volume, or at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume, or at least at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or even According to yet another embodiment, the ceramic filler may be at least about 54% by volume. The content of component 420 is about 57 volume percent or less based on the total volume of the dielectric coating 400; For example, it may be about 56% by volume or less, or even about 55% by volume or less. The content of component 220 is between and including any of the above minimum and maximum values. It will be appreciated that the content of the ceramic filler component 220 can be any value, including, but not limited to, It may be within a range between and including any of the above minimum and maximum values. Let's understand further.

[0053] According to yet another embodiment, the ceramic filler component 220 comprises a first For example, the content of the first filler material may be a ceramic filler. At least about 80% by volume, for example at least about 81% by volume, based on the total volume of component 220 %, or at least about 82% by volume, or at least about 83% by volume, or at least about 84% by volume. % by volume, or at least about 85% by volume, or at least about 86% by volume, or at least about 87% by volume, or at least about 88% by volume, or at least about 89% by volume, or even less According to yet another embodiment, the content of the first filler material is at least about 90% by volume. The amount is about 100% by volume or less based on the total volume of the ceramic filler component 220, for example About 99% by volume or less, or about 98% by volume or less, or about 97% by volume or less, or about 96% by volume or less or less than about 95% by volume, or less than about 94% by volume, or less than about 93% by volume, or even The content of the first filler material may be about 92% by volume or less. It will be appreciated that the value may be any value between and including any of the following: The content of the filler material shall be within and including any of the above minimum and maximum values. It will be further understood that the range may be within the range.

[0054] According to yet another embodiment, the ceramic filler component 220 is a second filler material. may include.

[0055] According to yet another embodiment, the second filler material of the ceramic filler component 220 is For example, the second filler material may include a high dielectric constant ceramic material, e.g. For example, the dielectric constant may include a ceramic material having a dielectric constant of at least about 14. According to the present invention, the second filler material of the ceramic filler component 220 can be any high dielectric constant ceramic. materials, e.g., TiO 2 , SrTiO 3 , ZrTi 2 O 6 , MgTiO 3 , CaTi O 3 , BaTiO 4 , or any combination thereof.

[0056] According to yet another embodiment, the second filler material of the ceramic filler component 220 is , TiO 2 According to yet another embodiment, the second filler material may include TiO 2 mosquito It could be.

[0057] According to yet another embodiment, the ceramic filler component 220 comprises a specific content of the second For example, the content of the second filler material may be a ceramic filler. at least about 1% by volume, for example at least about 2% by volume, based on the total volume of component 220; or at least about 3% by volume, or at least about 4% by volume, or at least about 5% by volume, or is at least about 6% by volume, or at least about 7% by volume, or at least about 8% by volume, or It may be at least about 9% by volume, or at least about 10% by volume. In other words, the content of the second filler material is based on the total volume of the ceramic filler component 220. About 20% by volume or less, for example, about 19% by volume or less, or about 18% by volume or less, or about 17% by volume or less % or less, or about 16% or less, or about 15% or less, or about 14% or less, or about The content of the second filler material may be about 13% by volume or less, or about 12% by volume or less. It may be any value between and including any of the minimum and maximum values ​​listed above. It will be understood that the content of the second filler material may be within any of the above minimum and maximum values. It will be further understood that the range may be between and including the above.

[0058] According to yet another embodiment, the ceramic filler component 220 has a certain content of amorphous For example, the ceramic filler component 220 may comprise at least about 98% may further comprise at least about 97%, such as at least about 99%, amorphous material. The content of the material may be any value between and including any of the values ​​listed above. It will be understood that the content of amorphous material may range between and including any of the values ​​recited above. It will be further understood that the range may be within the range.

[0059] According to other embodiments, the resin matrix component 210 may include certain materials. For example, the resin matrix component 210 can include a perfluoropolymer. Depending on the embodiment, the resin matrix component 410 may be comprised of a perfluoropolymer.

[0060] According to yet another embodiment, the perfluoropolymer of the resin matrix component 410 is , copolymers of tetrafluoroethylene (TFE), hexafluoropropylene (HFP ), a terpolymer of tetrafluoroethylene (TFE), or any of these. According to another embodiment, the resin matrix component 410 may include a combination of The fluoropolymers are copolymers of tetrafluoroethylene (TFE), hexafluoropropylene, copolymers of propylene (HFP), terpolymers of tetrafluoroethylene (TFE), Or any combination thereof.

[0061] According to yet another embodiment, the perfluoropolymer of the resin matrix component 410 is , polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (P FA), fluorinated ethylene propylene (FEP), or any combination thereof. According to yet another embodiment, the resin matrix component 410 is a perfluoropolymer. Polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin ( PFA), fluorinated ethylene propylene (FEP), or any combination thereof It could be.

[0062] According to yet another embodiment, the dielectric coating 200 is made of a resin matrix having a specific content. For example, the content of the resin matrix component 210 may be At least about 50% by volume, for example at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or at least In yet another embodiment, the cellulose acetate layer may be at least about 54% by volume, or even at least about 55% by volume. In other words, the content of the resin matrix component 210 is based on the total volume of the dielectric coating 200. or about 63% by volume or less, or about 62% by volume or less, or about 61% by volume or less, or about 60% by volume or less % or less, or about 59% or less, or about 58% or less, or even about 57% or less by volume. The content of the resin matrix component 210 is within any one of the above minimum and maximum values. It will be understood that the value may be any value between and including the above. The content of 210 is within the range including any of the above minimum and maximum values. It will be further appreciated that the present invention may be practiced in accordance with the present invention.

[0063] According to yet other embodiments, the dielectric coating 205 may include certain materials. For example, the content of perfluoropolymer in the total volume of the dielectric coating 405 is At least about 50% by volume, e.g., at least about 51% by volume, or at least about 52% by volume. %, or at least about 53% by volume, or at least about 54% by volume, or even at least According to yet another embodiment, the perfluoropolymer content may be about 55% by volume. , about 63% by volume or less, for example, about 62% by volume, based on the total volume of the dielectric coating 200 or less than about 61% by volume, or less than about 60% by volume, or less than about 59% by volume, or less than about 5 It may be less than 8% by volume, or even less than about 57% by volume. can be any value between and including any of the minimum and maximum values ​​listed above. It will be understood that the content of the perfluoropolymer is within the above minimum and maximum values. It will be further understood that the range may be between and including any of the above.

[0064] According to yet another embodiment, the dielectric coating 205 is measured using X-ray diffraction. For example, the porosity of the substrate 205 may be about 10% by volume or less, e.g. For example, about 9% by volume or less, or about 8% by volume or less, or about 7% by volume or less, or about 6% by volume or less The porosity of the dielectric coating 205 may be about 5% by volume or less. It will be understood that the dielectric constant may be any value between and including any of the values. The porosity of the body coating 205 may range between and including any of the values ​​listed above. It will be further appreciated that the present invention may be practiced in accordance with the present invention.

[0065] According to certain embodiments, the dielectric coating 205 may have a particular average thickness. For example, the average thickness of the dielectric coating 205 is at least about 0.1 microns, e.g. For example, at least about 0.5 microns, or at least about 1 micron, or at least about 2 microns. clons, or at least about 3 microns, or at least about 4 microns, or even less According to yet another embodiment, the thickness of the dielectric coating 205 may be about 5 microns. The average thickness is about 20 microns or less, for example, about 18 microns or less, or about 16 microns or less. or less than about 14 microns, or less than about 12 microns, or even less than about 10 microns The average thickness of the dielectric coating 205 may be within the range of the above minimum and maximum values. It will be appreciated that the dielectric coating may have any value between and including any of the above. The average thickness of the ring 405 is between and including any of the minimum and maximum values ​​listed above. It will be further understood that the range may be within the range.

[0066] According to yet another embodiment, the dielectric coating 205 is rated at 5 GHz and 20% RH. For example, the dielectric constant may be 0.01 to 0.15, and the dielectric constant may be 0.01 to 0.15. , the dielectric coating 205 may have a dielectric constant of about 0.005 or less, for example, about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less than about 0.0017, or less than about 0.0016, or less than about 0.0015, or The dielectric coating 205 may have a dissipation factor of about 0.0014 or less. It will be appreciated that the value may be any value between and including any of the above values. The dielectric loss tangent of the dielectric coating 205 may be any value between and including any of the above values. It will be further understood that the range may be inclusive.

[0067] According to yet another embodiment, the dielectric coating 205 is rated at 5 GHz and 80% RH. For example, a dielectric coating may have a specific dissipation factor (Df) measured in the range between 205 is about 0.005 or less, for example, about 0.004 or less, or about 0.003 or less, or About 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.00 17 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less The dielectric tangent of the dielectric coating 205 may be any one of the above values. It will be understood that the dielectric coating may be any value between and including the above. The dissipation factor of 205 may be within a range between and including any of the values ​​listed above. It will be further understood.

[0068] According to yet another embodiment, the dielectric coating 205 is rated at 10 GHz, 20% RH For example, a dielectric coating may have a particular dissipation factor (Df) measured in the range between 1000 and 10000 mm. The thickness 205 is about 0.005 or less, for example, about 0.004 or less, or about 0.003 or less, or is about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0 0.017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less The dielectric tangent of the dielectric coating 205 may be any one of the above values. It will be understood that the dielectric constant may be any value between and including any of the above. The dielectric loss tangent of the gauge 205 may be within a range between and including any of the values ​​listed above. It will be further understood that

[0069] According to yet another embodiment, the dielectric coating 205 is rated at 10 GHz, 80% RH For example, a dielectric coating may have a particular dissipation factor (Df) measured in the range between 1000 and 10000 mm. The thickness 205 is about 0.005 or less, for example, about 0.004 or less, or about 0.003 or less, or is about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0 0.017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less The dielectric tangent of the dielectric coating 205 may be any one of the above values. It will be understood that the dielectric constant may be any value between and including any of the above. The dielectric loss tangent of the gauge 205 may be within a range between and including any of the values ​​listed above. It will be further understood that

[0070] According to yet another embodiment, the dielectric coating 205 is rated at 28 GHz, 20% RH For example, a dielectric coating may have a particular dissipation factor (Df) measured in the range between 1000 and 10000 mm. The thickness 205 is about 0.005 or less, for example, about 0.004 or less, or about 0.003 or less, or is about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0 0.017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less The dielectric tangent of the dielectric coating 205 may be any one of the above values. It will be understood that the dielectric constant may be any value between and including any of the above. The dielectric loss tangent of the gauge 205 may be within a range between and including any of the values ​​listed above. It will be further understood that

[0071] According to yet another embodiment, the dielectric coating 205 is rated at 28 GHz, 80% RH For example, a dielectric coating may have a particular dissipation factor (Df) measured in the range between 1000 and 10000 mm. The thickness 205 is about 0.005 or less, for example, about 0.004 or less, or about 0.003 or less, or is about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0 0.017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less The dielectric tangent of the dielectric coating 205 may be any one of the above values. It will be understood that the dielectric constant may be any value between and including any of the above. The dielectric loss tangent of the gauge 205 may be within a range between and including any of the values ​​listed above. It will be further understood that

[0072] According to yet another embodiment, the dielectric coating 205 is rated at 39 GHz, 20% RH For example, a dielectric coating may have a particular dissipation factor (Df) measured in the range between 1000 and 10000 mm. The thickness 205 is about 0.005 or less, for example, about 0.004 or less, or about 0.003 or less, or is about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0 0.017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less The dielectric tangent of the dielectric coating 205 may be any one of the above values. It will be understood that the dielectric constant may be any value between and including any of the above. The dielectric loss tangent of the gauge 205 may be within a range between and including any of the values ​​listed above. It will be further understood that

[0073] According to yet another embodiment, the dielectric coating 205 is rated at 39 GHz, 80% RH For example, a dielectric coating may have a particular dissipation factor (Df) measured in the range between 1000 and 10000 mm. The thickness 205 is about 0.005 or less, for example, about 0.004 or less, or about 0.003 or less, or is about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0 0.017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less The dielectric tangent of the dielectric coating 205 may be any one of the above values. It will be understood that the dielectric constant may be any value between and including any of the above. The dielectric loss tangent of the gauge 205 may be within a range between and including any of the values ​​listed above. It will be further understood that

[0074] According to yet another embodiment, the dielectric coating 205 is %RH. The thickness 205 is about 0.005 or less, for example, about 0.004 or less, or about 0.003 or less. or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.00 The dielectric tangent of the dielectric coating 205 may be less than or equal to 14. It will be understood that the dielectric constant may be any value between and including any of the following: The dielectric tangent of the tinning 205 is within the range including any of the above values. It will be further understood that this is possible.

[0075] According to yet another embodiment, the dielectric coating 205 is adapted for use in a range of frequencies from 76 to 81 GHz, 80 %RH. The thickness 205 is about 0.005 or less, for example, about 0.004 or less, or about 0.003 or less. or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.00 The dielectric tangent of the dielectric coating 205 may be less than or equal to 14. It will be understood that the dielectric constant may be any value between and including any of the following: The dielectric tangent of the tinning 205 is within the range including any of the above values. It will be further understood that, according to yet another embodiment, the dielectric coating 20 5 is based on IPC-TM-650 2.4.24 Rev.C glass transition temperature and TMA For example, the dielectric coating may have a particular coefficient of thermal expansion measured according to the Z-axis thermal expansion of the dielectric coating. The ring 205 may have a coefficient of thermal expansion of about 80 ppm / ° C. or less.

[0076] According to yet another embodiment, the copper clad laminate 201 meets IPC-TM-650 2.4. Specific glass transition temperature and Z-axis thermal expansion measured according to Rev. C 24 For example, the copper clad laminate 201 may have a thermal expansion coefficient of about 45 ppm / ° C. or less. The number may be any number.

[0077] Any of the copper clad laminates described herein may be made by mixing the copper clad laminate coating and any copper foil. It will be understood that additional polymeric layers may be included between the layers. Thus, the additional polymer-based layer may include a filler as described herein. (i.e., a filled polymer layer), or may not contain a filler (i.e., an unfilled polymer layer). Rimar layer).

[0078] Turning now to the method of forming a printed circuit board, FIG. 3 includes a diagram illustrating a method 300 for forming a printed circuit board according to the embodiments. According to a particular embodiment, the forming method 300 includes a first step 310 of providing a copper foil layer. The resin matrix precursor component and the ceramic filler precursor component are combined to form a mixture. A second step 320 of forming an article and applying the formed mixture to a dielectric coating over the copper foil layer. and forming a copper clad laminate on a printed circuit board. and a fourth step 340 of forming on the substrate.

[0079] All descriptions, details, and characteristics provided herein with respect to the forming method 100 are incorporated by reference in their entirety. It will be understood that the above may further apply to or describe corresponding aspects of the method 300. Let's do it.

[0080] We will now turn to embodiments of printed circuit boards formed according to the method 300. 4 includes a diagram of a printed circuit board 400. As shown in FIG. The circuit board 400 includes a copper foil layer 402 and a dielectric coating 404 covering the surface of the copper foil layer 402. 05 and a copper clad laminate 401 which may include a dielectric coating 402. The coating 405 includes a resin matrix component 410 and a ceramic filler component 420. It can be seen.

[0081] Again, the dielectric coating 205 and / or the copper clad laminate 200 are All descriptions provided herein are based on the printed circuit board 200, including all of its components. It will be appreciated that further modifications of the circuit board 400 may be applied.

[0082] Many different aspects and embodiments are possible. After reading this specification, those skilled in the art will understand that these aspects and embodiments are It will be understood that these are merely illustrative examples and are not intended to limit the scope of the invention. The embodiment may be according to any one or more of the embodiments listed below.

[0083] Embodiment 1. A copper clad laminate comprising a copper foil layer and a dielectric coating covering the copper foil layer; the dielectric coating comprising a resin matrix component, a ceramic filler component, the ceramic filler component comprises a first filler material, and the dielectric coating comprises , a copper clad laminate having an average thickness of about 20 microns or less.

[0084] Embodiment 2. A copper clad laminate comprising a copper foil layer and a dielectric coating covering the copper foil layer; the dielectric coating comprising a resin matrix component, a ceramic filler component, The ceramic filler component comprises a first filler material, and A particle size distribution of at least about 0.2 microns and no greater than about D 1.6. 10 , at least about 0. 5 microns and D less than about 2.7 microns 50 and at least about 0.8 microns and D below 4.7 microns 90 4. A copper clad laminate comprising:

[0085] Embodiment 3. A copper clad laminate comprising a copper foil layer and a dielectric coating covering the copper foil layer; the dielectric coating comprising a resin matrix component, a ceramic filler component, the ceramic filler component comprises a first filler material, the first filler material , further comprising an average particle size of about 5 microns or less and a particle size distribution span (PSDS) of about 5 or less; PSDS is (D 90 -D 10 ) / D 50 is equal to D 90 D of the first filler material 90 D is equal to the particle size distribution measurement 10 D of the first filler material 10 Particle size distribution measurements Equally, D 50 D of the first filler material 50 Copper clad laminate, equal to particle size distribution measurements.

[0086] Embodiment 4. The particle size distribution of the first filler material is at least about 0.2 microns and about D below 1.6 10 The copper clad laminate of any one of claims 1, 2, and 3, comprising: .

[0087] Embodiment 5. The particle size distribution of the first filler material is at least about 0.5 microns and about D below 2.7 microns 50The copper according to any one of embodiments 1, 2 and 3, comprising Tension laminate.

[0088] Embodiment 6. The particle size distribution of the first filler material is at least about 0.8 microns and about D below 4.7 microns 90 The copper according to any one of embodiments 1, 2 and 3, comprising Tension laminate.

[0089] Embodiment 7. An embodiment of the present invention, wherein the first filler material further comprises an average particle size of about 10 microns or less. The copper-clad laminate according to embodiment 1.

[0090] Embodiment 8. An embodiment in which the first filler material comprises an average particle size of about 10 microns or less. The copper-clad laminate according to any one of aspects 1, 2, and 3.

[0091] Embodiment 9. The first filler material comprises a particle size distribution span (PSDS) of about 5 or less. ,PSDS,(D 90 -D 10 ) / D 50 is equal to D 90 However, the first filler material D 90 D is equal to the particle size distribution measurement 10 D of the first filler material 10 Particle size distribution measurements is equal to D 50 D of the first filler material 50 Equivalent to particle size distribution measurements, embodiment 1 4. The copper-clad laminate according to any one of claims 1 to 3.

[0092] Embodiment 10. The first filler material is about 10 m 2 / g or less. 4. The copper clad laminate of any one of embodiments 1, 2, and 3.

[0093] Embodiment 11. The method of embodiment 1, 2, or 3, wherein the first filler material comprises a silica-based compound. 3. The copper-clad laminate according to any one of claims 1 to 2.

[0094] Embodiment 12. Any of embodiments 1, 2, and 3, wherein the first filler material comprises silica. The copper clad laminate according to any one of the preceding claims.

[0095] Embodiment 13. The resin matrix of embodiments 1 and 2, which comprises a perfluoropolymer. 3. The copper-clad laminate according to any one of claims 1 to 2.

[0096] Embodiment 14. The perfluoropolymer is a copolymer of tetrafluoroethylene (TFE). copolymers of hexafluoropropylene (HFP), tetrafluoroethylene ( 14. The method of claim 13, comprising the step of: Copper clad laminate.

[0097] Embodiment 15. The perfluoropolymer is polytetrafluoroethylene (PTFE). , perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FE P), or any combination thereof.

[0098] Embodiment 16. The perfluoropolymer is polytetrafluoroethylene (PTFE). , perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FE P), or any combination thereof.

[0099] Embodiment 17: The content of the resin matrix component is 100% relative to the total volume of the dielectric coating. 5. The copper according to any one of claims 1, 2 and 3, Tension laminate.

[0100] Embodiment 18: The content of the resin matrix component is 100% relative to the total volume of the dielectric coating. 4. The copper clad laminate of any one of claims 1, 2, and 3, wherein the copper clad laminate has a thickness of about 63% or less by volume. Board.

[0101] Embodiment 19. The content of perfluoropolymer is based on the total volume of the dielectric coating. 14. The copper clad laminate of embodiment 13, wherein the copper clad laminate is at least about 50% by volume.

[0102] Embodiment 20. The content of perfluoropolymer is based on the total volume of the dielectric coating. 14. The copper clad laminate of embodiment 13, wherein the copper clad laminate has a thickness of about 63% or less by volume.

[0103] Embodiment 21. The content of the ceramic filler component is in the total volume of the dielectric coating. 4. The method according to any one of claims 1, 2, and 3, wherein the amount of the cellulose acetate solution is at least about 30% by volume. Copper clad laminate.

[0104] Embodiment 22. The content of the ceramic filler component is in the total volume of the dielectric coating. 4. The copper clad laminate of any one of claims 1, 2, and 3, wherein the copper clad laminate is about 57% by volume or less. Layer plate.

[0105] Embodiment 23. The content of the first filler material is based on the total volume of the ceramic filler component. 4. The method of claim 1, wherein the amount of the at least one ionic liquid is at least about 80% by volume. Copper clad laminate.

[0106] Embodiment 24. The content of the first filler material is based on the total volume of the ceramic filler component. 4. The copper clad laminate of any one of embodiments 1, 2, and 3, wherein the copper clad laminate is about 100% by volume or less. layer plate.

[0107] Embodiment 25. An embodiment in which the ceramic filler component further comprises a second filler material. The copper-clad laminate according to any one of aspects 1, 2, and 3.

[0108] Embodiment 26. The method of embodiment 25, wherein the second filler material comprises a high dielectric constant ceramic material. The copper-clad laminate according to claim 1.

[0109] Embodiment 27. A high dielectric constant ceramic material having a dielectric constant of at least about 14. The copper clad laminate according to embodiment 26.

[0110] Embodiment 28. The ceramic filler component is TiO 2 , SrTiO 3 , ZrTi 2 O 6 , MgTiO 3 , CaTiO 3 , BaTiO 4 or any combination thereof 27. The copper clad laminate of embodiment 26, comprising:

[0111] Embodiment 29. The content of the second filler material is based on the total volume of the ceramic filler component. 26. The copper clad laminate of embodiment 25, wherein the copper clad laminate has a copper content of at least about 1% by volume.

[0112] Embodiment 30. The content of the second filler material is based on the total volume of the ceramic filler component. 26. The copper clad laminate of embodiment 25, wherein the copper clad laminate has a volume ratio of about 20% or less.

[0113] Embodiment 31. A ceramic ceramic ceramic composition comprising: The copper clad laminate according to any one of embodiments 1, 2, and 3.

[0114] Embodiment 32. An embodiment in which the dielectric coating comprises no more than about 10% by volume porosity. 4. The copper-clad laminate according to any one of 1, 2, and 3.

[0115] Embodiment 33. The copper clad laminate of any one of embodiments 1, 2, or 3, wherein the copper clad laminate comprises about 10% by volume or less of porosity. 3. A copper-clad laminate according to any one of claims 1 to 3.

[0116] Embodiment 34. The dielectric coating comprises an average thickness of at least about 1 micron. 4. The copper clad laminate of any one of embodiments 1, 2, and 3.

[0117] Embodiment 35. An embodiment in which the dielectric coating comprises an average thickness of about 20 microns or less. 4. The copper clad laminate according to any one of aspects 1, 2, and 3.

[0118] Embodiment 36. The dielectric coating has a dissipation factor of about 3.5 or less (5 GHz, 20% 4. The copper clad laminate of any one of embodiments 1, 2, and 3, comprising:

[0119] Embodiment 37. The dielectric coating has a dissipation factor of about 0.001 or less (5 GHz, 2 4. The copper clad laminate of any one of embodiments 1, 2, and 3, comprising a temperature of 0% RH.

[0120] Embodiment 38. The dielectric coating has a coefficient of thermal expansion (all axes) of about 80 ppm / °C or less. The copper clad laminate of any one of embodiments 1, 2, and 3, comprising:

[0121] Embodiment 39. A copper clad laminate having at least about 600 nm between the copper foil layer and the dielectric coating. 4. The copper clad laminate of any one of claims 1, 2 and 3, comprising a peel strength of 100 lb / in. Board.

[0122] Embodiment 40. The dielectric coating of embodiment 1, wherein the dielectric coating has a moisture absorption of about 0.05% or less. 4. The copper-clad laminate according to any one of claims 1 to 3.

[0123] Embodiment 41. The method of embodiment 1, wherein the copper foil layer comprises an average thickness of at least about 6 microns. 4. The copper-clad laminate according to any one of 2 and 3.

[0124] Embodiment 42. The method of any one of embodiments 1, 2, or 3, wherein the copper foil layer comprises an average thickness of about 36 microns or less. 3. A copper-clad laminate according to any one of claims 1 to 3.

[0125] Embodiment 43. A printed circuit board comprising a copper clad laminate, the copper clad laminate comprising a copper foil a dielectric coating covering the copper foil layer, the dielectric coating being a resin matrix a filler component and a ceramic filler component, the filler component being a first The dielectric coating has an average thickness of 20 microns or less, and the dielectric coating includes a filler material. Lint circuit board.

[0126] Embodiment 44. A printed circuit board comprising a copper clad laminate, the copper clad laminate comprising a copper foil a dielectric coating covering the copper foil layer, the dielectric coating being a resin matrix a filler component and a ceramic filler component, the filler component being a first a first filler material having a particle size distribution of at least about 0.2 microns; Approximately 1.6 or less D 10 , D of at least about 0.5 microns and not more than about 2.7 microns 5 0 and D of at least about 0.8 microns and not more than about 4.7 microns. 90 Contains purine Circuit board.

[0127] Embodiment 45. A printed circuit board comprising a copper clad laminate, the copper clad laminate comprising a copper foil a dielectric coating covering the copper foil layer, the dielectric coating being a resin matrix a filler component and a ceramic filler component, the filler component being a first a first filler material having an average particle size of about 5 microns or less and a particle size of about 5 The particle size distribution span (PSDS) of 90 -D 10 ) / D 50 To Equally, D 90 D of the first filler material 90 D is equal to the particle size distribution measurement 10 But, 1. Filler material D 10 D is equal to the particle size distribution measurement 50 D of the first filler material 50 Printed circuit board, equal to particle size distribution measurements.

[0128] Embodiment 46. The particle size distribution of the first filler material is at least about 0.2 microns and D below about 1.6 10 The process according to any one of embodiments 43, 44 and 45, comprising Lint circuit board.

[0129] Embodiment 47. The particle size distribution of the first filler material is at least about 0.5 microns and D below about 2.7 microns 50 Any one of embodiments 43, 44, and 45, including The printed circuit board as described above.

[0130] Embodiment 48. The particle size distribution of the first filler material is at least about 0.8 microns and D below about 4.7 microns 90 Any one of embodiments 43, 44, and 45, including The printed circuit board as described above.

[0131] Embodiment 49. The first filler material further comprises an average particle size of about 10 microns or less. 46. ​​A printed circuit board according to any one of embodiments 43, 44, and 45.

[0132] Embodiment 50. The first filler material comprises an average particle size of about 10 microns or less. 46. ​​The printed circuit board of any one of aspects 43, 44, and 45.

[0133] Embodiment 51. The first filler material comprises a particle size distribution span (PSDS) of about 5 or less. PSDS is (D 90 -D 10 ) / D 50 is equal to D 90 The first filler material D 90 D is equal to the particle size distribution measurement 10 D of the first filler material 10 Particle size distribution measurement value is equal to D 50 D of the first filler material 50 Equivalent to particle size distribution measurement, embodiment 46. ​​A printed circuit board according to any one of 43, 44 and 45.

[0134] Embodiment 52. The first filler material is about 10 m 2 / g or less. 46. ​​A printed circuit board according to any one of embodiments 43, 44, and 45.

[0135] Embodiment 53. The first filler material comprises a silica-based compound. 45. A printed circuit board according to any one of claims 1 to 45.

[0136] Embodiment 54. The composition of any one of embodiments 43, 44, and 4, wherein the first filler material comprises silica. 5. A printed circuit board according to any one of claims 1 to 5.

[0137] Embodiment 55. The method of embodiment 43, wherein the resin matrix comprises a perfluoropolymer. 44 and 45. A printed circuit board according to any one of claims 1 to 45.

[0138] Embodiment 56. The perfluoropolymer is a copolymer of tetrafluoroethylene (TFE). copolymers of hexafluoropropylene (HFP), tetrafluoroethylene ( 56. The method of claim 55, comprising the step of: Printed circuit board.

[0139] Embodiment 57. The perfluoropolymer is polytetrafluoroethylene (PTFE). , perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FE P), or any combination thereof.

[0140] Embodiment 58. The perfluoropolymer is polytetrafluoroethylene (PTFE). , perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FE P), or any combination thereof. .

[0141] Embodiment 59. The content of the resin matrix component is relative to the total volume of the dielectric coating. 46. ​​The method of any one of embodiments 43, 44, and 45, wherein the at least one of the at least one The printed circuit board.

[0142] Embodiment 60: The content of the resin matrix component is 100% relative to the total volume of the dielectric coating. 46. ​​The process according to any one of embodiments 43, 44, and 45, wherein the amount of the cellulose is about 63% or less by volume. Lint circuit board.

[0143] Embodiment 61. The content of perfluoropolymer is based on the total volume of the dielectric coating 56. The printed circuit board of embodiment 55, wherein the thickness is at least about 50% by volume.

[0144] Embodiment 62. The content of perfluoropolymer is based on the total volume of the dielectric coating. 56. The printed circuit board of embodiment 55, wherein the thickness of the printed circuit board is about 63% or less by volume.

[0145] Embodiment 63. The content of the ceramic filler component is in the total volume of the dielectric coating. 46. ​​Any one of embodiments 43, 44, and 45, wherein the amount of the at least one ionic component is at least about 50% by volume. The printed circuit board as described above.

[0146] Embodiment 64. The content of the ceramic filler component in the total volume of the dielectric coating 46. ​​The method of any one of embodiments 43, 44, and 45, wherein the amount of the cellulose acetate solution is about 57% or less by volume. Printed circuit board.

[0147] Embodiment 65. The content of the first filler material is based on the total volume of the ceramic filler component. 46. ​​Any one of embodiments 43, 44, and 45, wherein the amount of the cellulose acetate layer is at least about 80% by volume. The printed circuit board as described above.

[0148] Embodiment 66. The content of the first filler material is based on the total volume of the ceramic filler component. 46. ​​The method of any one of embodiments 43, 44, and 45, wherein the amount of the cellulose acetate solution is about 100% or less by volume. printed circuit board.

[0149] Embodiment 67. An embodiment in which the ceramic filler component further comprises a second filler material. 46. ​​The printed circuit board according to any one of claims 43, 44, and 45.

[0150] Embodiment 68. The method of embodiment 6, wherein the second filler material comprises a high dielectric constant ceramic material. 8. The printed circuit board according to claim 7.

[0151] Embodiment 69. A high dielectric constant ceramic material having a dielectric constant of at least about 14. 69. The printed circuit board of embodiment 68.

[0152] Embodiment 70. The ceramic filler component is TiO 2 , SrTiO 3 , ZrTi 2 O 6 , MgTiO 3 , CaTiO 3 , BaTiO 4 or any combination thereof 69. The printed circuit board of embodiment 68, comprising:

[0153] Embodiment 71. The content of the second filler material is based on the total volume of the ceramic filler component. 68. The printed circuit board of embodiment 67, wherein the surface area of ​​the printed circuit board is at least about 1% by volume.

[0154] Embodiment 72. The content of the second filler material is based on the total volume of the ceramic filler component. 68. The printed circuit board of embodiment 67, wherein the surface area of ​​the printed circuit board is about 20% or less by volume.

[0155] Embodiment 73. A ceramic ceramic ceramic composition comprising a ceramic filler component that is at least about 97% amorphous. 46. ​​The printed circuit board according to any one of embodiments 43, 44, and 45.

[0156] Embodiment 74. An embodiment in which the dielectric coating comprises no more than about 10% by volume porosity. 46. ​​A printed circuit board according to any one of 43, 44 and 45.

[0157] Embodiment 75. The copper clad laminate of any one of embodiments 43 and 4, wherein the copper clad laminate comprises about 10% by volume or less of porosity. 4 and 45. A printed circuit board according to any one of claims 1 to 4.

[0158] Embodiment 76. The dielectric coating comprises an average thickness of at least about 1 micron. 46. ​​A printed circuit board according to any one of embodiments 43, 44, and 45.

[0159] Embodiment 77. An embodiment in which the dielectric coating comprises an average thickness of about 20 microns or less. 46. ​​The printed circuit board of any one of aspects 43, 44, and 45.

[0160] Embodiment 78. The dielectric coating has a dissipation factor of about 0.005 or less (5 GHz, 2 46. ​​The printed circuit of any one of embodiments 43, 44, and 45, comprising a refrigerant having a temperature of 0% RH. substrate.

[0161] Embodiment 79. The dielectric coating has a dissipation factor of about 0.0014 or less (5 GHz, 20% RH)。 The print cycle of any one of embodiments 43, 44, and 45, comprising: Road board.

[0162] Embodiment 80. The dielectric coating has a coefficient of thermal expansion (all axes) of about 80 ppm / °C or less. 46. ​​The printed circuit board of any one of embodiments 43, 44, and 45, comprising:

[0163] Embodiment 81. A copper clad laminate having at least about 600 nm between the copper foil layer and the dielectric coating. 46. ​​The process of any one of claims 43, 44, and 45, comprising a peel strength of 100 lb / in. Lint circuit board.

[0164] Embodiment 82. The dielectric coating of embodiment 4, wherein the dielectric coating has a moisture absorption of about 0.05% or less. 3, 44, and 45. A printed circuit board according to any one of claims 3, 44, and 45.

[0165] Embodiment 83. The method of embodiment 43, wherein the copper foil layer comprises an average thickness of at least about 6 microns. 46. ​​A printed circuit board according to any one of claims 44 and 45.

[0166] Embodiment 84. The method of embodiment 43, 4, or any of the preceding embodiments, wherein the copper foil layer comprises an average thickness of about 36 microns or less. 4 and 45. A printed circuit board according to any one of claims 1 to 4.

[0167] Embodiment 85. A method of forming a copper clad laminate, comprising providing a copper foil layer and applying a resin The matrix precursor component and the ceramic filler precursor component are combined to form a forming mixture. and forming the forming mixture into a dielectric coating over the copper foil. wherein the dielectric coating has an average thickness of about 20 microns or less.

[0168] Embodiment 86. A method of forming a copper clad laminate, comprising providing a copper foil layer and applying a resin The matrix precursor component and the ceramic filler precursor component are combined to form a forming mixture. and forming the forming mixture into a dielectric coating over the copper foil. The ceramic filler precursor component includes a first filler precursor material, and the first filler The particle size distribution of the precursor material is at least about 0.2 microns and not more than about 1.6 microns, D 1 0 , D of at least about 0.5 microns and not more than about 2.7 microns 50 , and at least about D 0.8 microns and less than or equal to about 4.7 microns 90 A method comprising:

[0169] Embodiment 87. A method of forming a copper clad laminate, comprising providing a copper foil layer and applying a resin The matrix precursor component and the ceramic filler precursor component are combined to form a forming mixture. and forming the forming mixture into a dielectric coating over the copper foil. The ceramic filler precursor component includes a first filler precursor material, and the first filler The precursor material has an average particle size of about 5 microns or less and a particle size distribution span (PSDS) of about 5 or less. The PSDS further includes: 90 -D 10 ) / D 50 is equal to D 90 But the first phi D of precursor materials 90 D is equal to the particle size distribution measurement 10 A first filler precursor material D 10 D is equal to the particle size distribution measurement 50 D of the first filler precursor material 50 Particle size Method equal to fabric measurements.

[0170] Embodiment 88. The particle size distribution of the first filler precursor material is at least about 0.2 microns. and D of about 1.6 microns or less 10 Any of embodiments 85, 86, and 87, including The method described in one.

[0171] Embodiment 89. The particle size distribution of the first filler precursor material is at least about 0.5 microns. and D less than about 2.7 microns 50 Any of embodiments 85, 86, and 87, including The method described in one.

[0172] Embodiment 90. The particle size distribution of the first filler precursor material is at least about 0.8 microns. and D less than about 4.7 microns 90 Any of embodiments 85, 86, and 87, including The method described in one.

[0173] Embodiment 91. The first filler precursor material further comprises an average particle size of about 10 microns or less. 86. The method of embodiment 85, comprising:

[0174] Embodiment 92. The first filler precursor material comprises an average particle size of about 10 microns or less. , The method according to any one of embodiments 85, 86, and 87.

[0175] Embodiment 93. The first filler precursor material has a particle size distribution span (PSDS) of about 5 or less. ) and the PSDS is (D 90 -D 10 ) / D 50 is equal to D 90 But the first Phil -D of precursor material 90 D is equal to the particle size distribution measurement 10 of the first filler precursor material D 10 D is equal to the particle size distribution measurement 50 D of the first filler precursor material 50 Particle size distribution The method of any one of embodiments 85, 86, and 87, wherein the measured value is equal to the measured value.

[0176] Embodiment 94. A first filler precursor material is about 10 m 2 / g or less average surface area 88. The method of any one of embodiments 85, 86, and 87, comprising:

[0177] Embodiment 95. The first filler precursor material comprises a silica-based compound. 86, or 87.

[0178] Embodiment 96. Any of embodiments 85, 86, or any ...7, 89, or 90, wherein the first filler precursor material comprises silica. 87. The method according to any one of claims 87 to 87.

[0179] Embodiment 97. The resin matrix precursor component comprises a perfluoropolymer. 88. The method of any one of embodiments 85, 86, and 87.

[0180] Embodiment 98. The perfluoropolymer is a copolymer of tetrafluoroethylene (TFE). copolymers of hexafluoropropylene (HFP), tetrafluoroethylene ( 98. The method of claim 97, comprising the step of: method.

[0181] Embodiment 99. The perfluoropolymer is polytetrafluoroethylene (PTFE). , perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FE P), or any combination thereof.

[0182] Embodiment 100. The perfluoropolymer is polytetrafluoroethylene (PTFE ), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (F EP), or any combination thereof.

[0183] Embodiment 101. The content of the resin matrix precursor component is less than the total content of the dielectric coating. Any of embodiments 85, 86, and 87, wherein the amount is at least about 50% by volume. The method described in one.

[0184] Embodiment 102. The content of the resin matrix precursor component is less than the total content of the dielectric coating. 88. Any one of embodiments 85, 86, and 87, wherein the amount of the cellulose acetate layer is about 63% or less by volume. The method described.

[0185] Embodiment 103. The content of perfluoropolymer in the total volume of the dielectric coating 98. The method of embodiment 97, wherein the amount of the at least one polymer is at least about 50% by volume.

[0186] Embodiment 104. The content of perfluoropolymer in the total volume of the dielectric coating 98. The method of embodiment 97, wherein the amount of the cellulose acetate solution is about 63% or less by volume.

[0187] Embodiment 105. The content of the ceramic filler precursor component is Any of embodiments 85, 86, and 87, wherein the total volume is at least about 50% by volume. or one of the methods described above.

[0188] Embodiment 106. The content of the ceramic filler precursor component is Any one of embodiments 85, 86, and 87, wherein the amount is about 57% by volume or less based on the total volume. The method described above.

[0189] Embodiment 107. The content of the first filler precursor material is a ceramic filler precursor. 88. The composition of claim 85, 86, or 87, wherein the amount of the component is at least about 80% by volume based on the total volume of the components. The method according to any one of the preceding claims.

[0190] Embodiment 108. The content of the first filler precursor material is a ceramic filler precursor. Any of embodiments 85, 86, and 87, wherein the amount of the component is about 100% by volume or less based on the total volume of the components. The method according to any one of the preceding claims.

[0191] Embodiment 109. A ceramic filler precursor component further comprises a second filler precursor material. 88. The method of any one of embodiments 85, 86, and 87, comprising:

[0192] Embodiment 110. A method according to the present invention, wherein the second filler precursor material comprises a high dielectric constant ceramic material. The method of embodiment 109.

[0193] Embodiment 111. The high dielectric constant ceramic material has a dielectric constant of at least about 14. The method of embodiment 110.

[0194] Embodiment 112. The ceramic filler precursor component is TiO 2 , SrTiO 3 , Zr Ti 2 O 6 , MgTiO 3 , CaTiO 3 , BaTiO 4 or any combination thereof The method of embodiment 110, further comprising:

[0195] Embodiment 113. The content of the second filler precursor material is a ceramic filler precursor. 110. The method of embodiment 109, wherein the amount of the component is at least about 1% by volume based on the total volume of the ingredients.

[0196] Embodiment 114. The content of the second filler precursor material is a ceramic filler precursor. 110. The method of embodiment 109, wherein the amount is about 20% by volume or less based on the total volume of the ingredients.

[0197] Embodiment 115. The ceramic filler precursor component is at least about 97% amorphous. 88. The method of any one of embodiments 85, 86, and 87,

[0198] Embodiment 116. An embodiment in which the dielectric coating comprises about 10% by volume or less of porosity. 88. The method according to any one of aspects 85, 86, and 87.

[0199] Embodiment 117. The method of embodiment 85, wherein the copper clad laminate comprises a porosity of about 10% by volume or less. 86 and 87. A method according to any one of claims 86 and 87.

[0200] Embodiment 118. The dielectric coating comprises an average thickness of at least about 1 micron. , The method according to any one of embodiments 85, 86, and 87.

[0201] Embodiment 119. A method according to claim 1, wherein the dielectric coating comprises an average thickness of about 20 microns or less. 88. The method according to any one of embodiments 85, 86, and 87.

[0202] Embodiment 120. The dielectric coating has a dissipation factor of about 0.005 or less (5 GHz, 88. The method of any one of embodiments 85, 86, and 87, comprising:

[0203] Embodiment 121. The dielectric coating has a dissipation factor of about 0.0014 or less (5 GHz 88. The method of any one of embodiments 85, 86, and 87, comprising:

[0204] Embodiment 122. The dielectric coating has a thermal expansion coefficient of about 80 ppm / °C or less (all axes). 88. The method of any one of embodiments 85, 86, and 87, comprising:

[0205] Embodiment 123. A copper clad laminate having at least about 1000 .mu.m between the copper foil layer and the dielectric coating. 88. The method of any one of claims 85, 86, and 87, comprising a peel strength of 6 lb / in. method.

[0206] Embodiment 124. An embodiment in which the dielectric coating comprises no more than about 0.05% moisture absorption. 85. A method according to any one of 85, 86 and 87.

[0207] Embodiment 125. The method of embodiment 8, wherein the copper foil layer comprises an average thickness of at least about 6 microns. 5, 86, and 87.

[0208] Embodiment 126. The embodiment 85, wherein the copper foil layer comprises an average thickness of about 36 microns or less. 86 and 87. A method according to any one of claims 86 and 87.

[0209] Embodiment 127. A method of forming a printed circuit board, comprising providing a copper foil layer. The resin matrix precursor component and the ceramic filler precursor component are mixed together to form a mixture. forming a mixture and forming the mixture into a dielectric coating over the copper foil. wherein the dielectric coating has an average thickness of about 20 microns or less.

[0210] Embodiment 128. A method of forming a printed circuit board, comprising providing a copper foil layer. The resin matrix precursor component and the ceramic filler precursor component are mixed together to form a mixture. forming a mixture and forming the mixture into a dielectric coating over the copper foil. the ceramic filler precursor component comprises a first filler precursor material, and The particle size distribution of the filler precursor material is at least about 0.2 microns and no greater than about 1.6 microns. D below 10 , D of at least about 0.5 microns and not more than about 2.7 microns 50 , and a few D at least about 0.5 microns and not more than about 4.7 microns 90 A method comprising:

[0211] Embodiment 129. A method of forming a printed circuit board, comprising providing a copper foil layer. The resin matrix precursor component and the ceramic filler precursor component are mixed together to form a mixture. forming a mixture and forming the mixture into a dielectric coating over the copper foil. the ceramic filler precursor component comprises a first filler precursor material, and The filler precursor material has an average particle size of about 5 microns or less and a particle size distribution span (P SDS) and PSDS (D 90 -D 10 ) / D 50 is equal to D 90 But, 1. Filler precursor material D 90 D is equal to the particle size distribution measurement 10 But before the first filler D of the core material 10 D is equal to the particle size distribution measurement 50 D of the first filler precursor material 5 0 Equivalent to particle size distribution measurement, method.

[0212] Embodiment 130. The particle size distribution of the first filler precursor material is at least about 0.2 microns. Long and less than 1.6 microns D 10 The method of any one of embodiments 127, 128, and 129, including The method according to any one of the preceding claims.

[0213] Embodiment 131. The particle size distribution of the first filler precursor material is at least about 0.5 microns. Long and less than 2.7 microns D 50 The method of any one of embodiments 127, 128, and 129, including The method according to any one of the preceding claims.

[0214] Embodiment 132. The particle size distribution of the first filler precursor material is at least about 0.8 microns. Long and less than 4.7 microns D 90 The method of any one of embodiments 127, 128, and 129, including The method according to any one of the preceding claims.

[0215] Embodiment 133. The first filler precursor material has an average particle size of about 10 microns or less. 133. The method of embodiment 132, comprising:

[0216] Embodiment 134. The first filler precursor material comprises an average particle size of about 10 microns or less. The method according to any one of embodiments 127, 128, and 129.

[0217] Embodiment 135. The first filler precursor material has a particle size distribution span (PSD) of about 5 or less. S) and PSDS is (D 90 -D 10 ) / D 50 is equal to D 90 But the first phi D of precursor materials 90 D is equal to the particle size distribution measurement 10 A first filler precursor material D 10 D is equal to the particle size distribution measurement 50 D of the first filler precursor material 50 Particle size 130. The method of any one of embodiments 127, 128, and 129, wherein the measurement is equal to the fabric measurement.

[0218] Embodiment 136. The first filler precursor material is about 10 m 2 / g or less average surface area The method of any one of embodiments 127, 128, and 129, further comprising:

[0219] Embodiment 137. The method of embodiment 1, wherein the first filler precursor material comprises a silica-based compound. 27, 128, or 129.

[0220] Embodiment 138. The method of embodiment 127, wherein the first filler precursor material comprises silica. 28 and 129.

[0221] Embodiment 139. A method according to the present invention, wherein the resin matrix precursor component comprises a perfluoropolymer. The method according to any one of embodiments 127, 128, and 129.

[0222] Embodiment 140. The perfluoropolymer is a copolymer of tetrafluoroethylene (TFE). Polymer, copolymer of hexafluoropropylene (HFP), tetrafluoroethylene (TFE), terpolymers thereof, or any combination thereof. Method of posting.

[0223] Embodiment 141. The perfluoropolymer is polytetrafluoroethylene (PTFE ), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (F EP), or any combination thereof.

[0224] Embodiment 142. The perfluoropolymer is polytetrafluoroethylene (PTFE ), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (F EP), or any combination thereof.

[0225] Embodiment 143. The content of the resin matrix precursor component is less than the total content of the dielectric coating. Any of embodiments 127, 128, and 129, wherein the volume is at least about 50% by volume. The method according to any one of the above.

[0226] Embodiment 144. The content of the resin matrix precursor component is less than the total content of the dielectric coating. Any of embodiments 127, 128, and 129, wherein the amount of the ionic liquid is about 63% or less by volume. The method described in one.

[0227] Embodiment 145. The content of perfluoropolymer in the total volume of the dielectric coating 140. The method of embodiment 139, wherein the amount of the at least one polymer is at least about 50% by volume.

[0228] Embodiment 146. The content of perfluoropolymer in the total volume of the dielectric coating 140. The method of embodiment 139, wherein the amount of the cellulose acetate layer is about 63% or less by volume.

[0229] Embodiment 147. The content of the ceramic filler precursor component is At least about 30% by volume of the total volume of embodiments 127, 128, and 129. The method according to any one of the preceding claims.

[0230] Embodiment 148. The content of the ceramic filler precursor component is Any of embodiments 127, 128, and 129, wherein the total volume of the or one of the methods described above.

[0231] Embodiment 149. The content of the first filler precursor material is a ceramic filler precursor. At least about 80% by volume based on the total volume of the ingredients, as in embodiments 127, 128, and 1 29. The method according to any one of claims 29 to 30.

[0232] Embodiment 150. The content of the first filler precursor material is a ceramic filler precursor. 100% by volume or less based on the total volume of the components. 2. The method according to claim 1 ,

[0233] Embodiment 151. A ceramic filler precursor component further comprises a second filler precursor material. 130. The method of any one of embodiments 127, 128, and 129, comprising:

[0234] Embodiment 152. A method according to the present invention, wherein the second filler precursor material comprises a high dielectric constant ceramic material. The method according to embodiment 151.

[0235] Embodiment 153. The high dielectric constant ceramic material has a dielectric constant of at least about 14. The method of embodiment 152.

[0236] Embodiment 154. The ceramic filler precursor component is TiO 2 , SrTiO 3 , Zr Ti 2 O 6 , MgTiO 3 , CaTiO 3 , BaTiO 4 or any combination thereof 153. The method of embodiment 152, further comprising:

[0237] Embodiment 155. The content of the second filler precursor material is a ceramic filler precursor. The method of embodiment 151, wherein the amount of the component is at least about 1% by volume based on the total volume of the ingredients.

[0238] Embodiment 156. The content of the second filler precursor material is a ceramic filler precursor. The method of embodiment 151, wherein the amount of the component is about 20% by volume or less, based on the total volume of the components.

[0239] Embodiment 157. The ceramic filler precursor component is at least about 97% amorphous. The method according to any one of embodiments 127, 128, and 129.

[0240] Embodiment 158. An embodiment in which the dielectric coating comprises no more than about 10% by volume porosity. 129. The method according to any one of aspects 127, 128, and 129.

[0241] Embodiment 159. The copper clad laminate of embodiment 127, wherein the copper clad laminate comprises about 10% by volume or less of porosity. 128 and 129.

[0242] Embodiment 160. The dielectric coating comprises an average thickness of at least about 1 micron. , A method according to any one of embodiments 127, 128 and 129.

[0243] Embodiment 161. A method according to claim 1, wherein the dielectric coating comprises an average thickness of about 20 microns or less. The method according to any one of embodiments 127, 128, and 129.

[0244] Embodiment 162. The dielectric coating has a dissipation factor of about 0.005 or less (5 GHz, 20% RH)。 The method of any one of embodiments 127, 128, and 129, comprising: Law.

[0245] Embodiment 163. The dielectric coating has a dissipation factor of about 0.0014 or less (at 5 GHz 130. The method of any one of embodiments 127, 128, and 129, comprising the steps of: method.

[0246] Embodiment 164. The dielectric coating has a coefficient of thermal expansion (all axes) of about 80 ppm / °C or less. 130. The method of any one of embodiments 127, 128, and 129, comprising:

[0247] Embodiment 165. A copper clad laminate having at least about 1000 .mu.m between the copper foil layer and the dielectric coating. Any one of embodiments 127, 128, and 129, including a peel strength of 6 lb / in. The method described.

[0248] Embodiment 166. An embodiment in which the dielectric coating comprises no more than about 0.05% moisture absorption. 127, 128, or 129.

[0249] Embodiment 167. The method of embodiment 1, wherein the copper foil layer comprises an average thickness of at least about 6 microns. 27, 128, or 129.

[0250] Embodiment 168. The method of embodiment 127, wherein the copper foil layer comprises an average thickness of about 36 microns or less. 128 and 129.

[0251] Not all of the activities described above in the general description or examples are required, and specific Some of the activities may not be required and one or more further activities may be performed in addition to the activities listed. Furthermore, the order in which the activities are listed does not necessarily indicate the order in which they are performed. This is not the order in which they are displayed.

[0252] Benefits, other advantages, and solutions to problems have been described above with regard to specific embodiments. However, benefits, advantages, solutions to problems, and any benefits, advantages, or solutions that bring Any feature that may render the invention more prominent or prominent may be added to any or all of the important, essential features of the claims. These terms should not be construed as essential or essential features of the present invention.

[0253] The specification and illustrations of the embodiments set forth herein are provided to provide a general understanding of the structure of the various embodiments. The specification and illustrations are intended to provide a solution to the problems described herein. Serves as a comprehensive and comprehensive description of all elements and features of the devices and systems used It is not intended that separate embodiments be provided in combination in a single embodiment. Conversely, various embodiments that are described in the context of a single embodiment for brevity may be combined together. The features may be provided separately or in any subcombination. Reference to a range of values ​​includes every individual value within that range. Structural and logical substitutions may be made without departing from the scope of the present disclosure. Other embodiments may be used and derived from this disclosure, as may be modified or otherwise altered. Accordingly, the present disclosure should be regarded as illustrative and not restrictive. It is.

Claims

1. A copper clad laminate comprising: a copper foil layer and a dielectric coating covering the copper foil layer, Gu, A resin matrix component; a ceramic filler component, The ceramic filler component includes a first filler material, and the dielectric coating The copper clad laminate has an average thickness of about 20 microns or less.

2. 10. The method of claim 1, wherein the first filler material further comprises an average particle size of about 10 microns or less. The copper clad laminate described herein.

3. The first filler material comprises a particle size distribution span (PSDS) of about 5 or less, S is (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler material 9 0 D is equal to the particle size distribution measurement 10 is the D of the first filler material 10 Particle size distribution measurements is equal to D 50 is the D of the first filler material 50 Equivalent to particle size distribution measurement, claim 2. The copper-clad laminate according to claim 1.

4. The first filler material is about 10 m 2 10. The method of claim 1, further comprising the step of: The copper-clad laminate according to claim 1.

5. The copper clad laminate of claim 1 , wherein the first filler material comprises a silica-based compound.

6. The copper clad laminate of claim 1 , wherein the first filler material comprises silica.

7. 10. The copper clad laminate of claim 1, wherein the resin matrix comprises a perfluoropolymer. Board.

8. The content of the resin matrix component is small relative to the total volume of the dielectric coating.

2. The copper clad laminate of claim 1, wherein the copper clad laminate has a thickness of at least about 50% by volume and no more than about 63% by volume.

9. The content of the ceramic filler component relative to the total volume of the dielectric coating is 10. The copper clad laminate of claim 1, wherein the copper clad laminate is at least about 30% by volume and no more than about 57% by volume.

10. The content of the first filler material is based on the total volume of the ceramic filler component.

10. The copper clad laminate of claim 1, wherein the copper clad laminate is at least about 80% by volume and no more than about 100% by volume.

11. The dielectric coating has a dissipation factor (tangent) of about 3.5 or less (5 GHz, 20% RH). The copper clad laminate of claim 1 .

12. A printed circuit board comprising a copper clad laminate, the copper clad laminate comprising: a copper foil layer and a dielectric coating covering the copper foil layer, Gu, A resin matrix component; a ceramic filler component, the ceramic filler component comprises a first filler material; The dielectric coating has an average thickness of 20 microns or less. Road board.

13. 13. The method of claim 12, wherein the first filler material further comprises an average particle size of about 10 microns or less. The printed circuit board according to claim 1.

14. The first filler material comprises a particle size distribution span (PSDS) of about 5 or less, S is (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler material 9 0 D is equal to the particle size distribution measurement 10 is the D of the first filler material 10 Particle size distribution measurements is equal to D 50 is the D of the first filler material 50 Equivalent to particle size distribution measurement, claim 13. The printed circuit board according to claim 12.

15. 1. A method of forming a copper clad laminate, the method comprising: Providing a copper foil layer; The resin matrix precursor component and the ceramic filler precursor component are combined to form a mixture. forming a compound; and forming the forming mixture into a dielectric coating over the copper foil; The method, wherein the dielectric coating has an average thickness of about 20 microns or less.

Citation Information

Patent Citations

  • Fluoropolymer composite material containing at least two ceramic fillers in order to adjust dielectric constant and dimensional stability independently

    JP1996059942A

  • Sheet-like molded article and laminate

    JP2001181517A

  • Sheet-like molding and laminate

    JP2002100238A

  • Resin composition for printed wiring board, prepreg, laminate, and printed wiring board using the same

    JP2009138201A

  • Resin composition for printed wiring board, prepreg for printed wiring board, laminate, metal-clad laminate, printed wiring board and magnesium oxide

    JP2016003260A